Upregulation of Surface Feline CXCR4 Expression following Ectopic Expression of CCR5: Implications for Studies of the Cell Tropism of Feline Immunodeficiency Virus - Willett, Brian J. (American Society for Microbiology, 2002)
Feline CXCR4 and CCR5 were expressed in feline cells as fusion proteins with enhanced green fluorescent protein (EGFP). Expression of the EGFP fusion proteins was localized to the cell membrane, and surface expression of CXCR4 was confirmed by using a cross-species-reactive anti-CXCR4 monoclonal antibody. Ectopic expression of feline CCR5 enhanced expression of either endogenous feline CXCR4 or exogenous feline or human CXCR4 expressed from a retrovirus vector, indicating that experiments investigating the effect of CCR5 expression on feline immunodeficiency virus (FIV) infection must be interpreted with caution. Susceptibility to infection with cell culture-adapted strains of FIV or to syncytium formation following transfection with a eukaryotic vector expressing an env gene from a cell culture-adapted strain of virus correlated with expression of either human or feline CXCR4, whereas feline CCR5 had no effect. In contrast, neither CXCR4 nor CCR5 rendered cells permissive to either productive infection with primary strains of FIV or syncytium formation following transfection with primary env gene expression vectors. Screening a panel of Ghost cell lines expressing diverse human chemokine receptors confirmed that CXCR4 alone supported fusion mediated by the FIV Env from cell culture-adapted viruses. CXCR4 expression was upregulated in Ghost cells coexpressing CXCR4 and CCR5 or CXCR4, CCR5, and CCR3, and susceptibility to FIV infection could be correlated with the level of CXCR4 expression. The data suggest that β-chemokine receptors may influence FIV infection by modulating the expression of CXCR4.